In vitro investigation of elevated hemolysis susceptibility in neonatal blood - Heyer, Jan; Volmering, Stella; Hoyos-Banchon, Camila; Koc, Sarah; Jeremiah, Lydia; Steinseifer, Ulrich; Orlikowsky, Thorsten; Jansen, Sebastian V.; Clauser, Johanna C.; Schoberer, Mark (Frontiers in Pediatrics, 2025)
IntroductionHemolysis is a relevant complication and is responsible for morbidity and mortality of neonatal extracorporeal membrane oxygenation (ECMO) therapy. For novel therapies like artificial placenta, hemolysis could also lead to complications or therapy failure, especially since the targeted patients are born at the borderline of viability. Standardized in vitro blood testing using animal blood is commonly used to assess the hemolytic potential of newly developed systems during their design and development. However, neonatal human blood differs from animal blood. For example, neonatal blood exhibits a higher erythrocyte volume, lower overall viscosity, and greater erythrocyte elasticity. This study investigates whether the porcine blood analog, commonly used in standardized protocols, can also be used to assess hemolysis in neonatal blood.MethodsHuman neonatal blood was harvested from placentas and umbilical cords of neonates born by cesarean section. Porcine blood was obtained from a local abattoir. Both collection processes followed predefined standardized protocols. Normalized Index for hemolysis (NIH) was calculated based on determined free plasma hemoglobin.ResultThere was a significantly (p < 0.05) higher normalized index of hemolysis in the human neonatal blood group (NIH=0.165 g 100 L−1; SD=0.082) compared to the porcine group (NIH=0.101 g 100l−1; SD=0.038). In contrast, under static reference conditions, neonatal blood exhibited lower hemolysis (NIH=0.025 g 100 L−1; SD=0.018) than porcine blood (NIH=0.055 g 100l−1; SD=0.038).DiscussionIn standardized in vitro hemolysis testing, porcine blood might not serve as a suitable analog for human neonatal blood, as it significantly underestimates the hemolysis potential observed in neonatal blood.